The global crisis : causes, responses and challenges. (International Labour Office, 2011)
"The crisis which erupted in the financial systems of developed countries in the autumn of 2008 quickly affected all economies throughout the world. The result was job losses, enterprise bankruptcies and cuts in the incomes of millions of people. Quickly after the start of the crisis, the ILO engaged in a research programme in order to shed light on its origins, help devise policy remedies and assess crisis responses at both national and international levels. One of the outcomes of this research was to provide analytical background to the Global Jobs Pact endorsed by ILO constituents in June 2009. The purpose of this collection of essays is to put together the main lessons from ILO research since the start of the global crisis."--Introduction.